Load transfer mechanisms in geotextile-reinforced embankments overlying voids: Experimental and analytical approaches. Issue 3 (June 2016) - Huckert, Audrey; Briançon, Laurent; Villard, Pascal; Garcin, Patrick
Abstract: The techniques of soil reinforcement by geotextile are easy and economic solutions that limit the surface settlements of embankments prone to sinkholes. The design of such structures is based on understanding complex mechanisms, such as the tensile geosynthetic behavior under vertical loading, the frictional interaction between the soil and the reinforcement, the load transfer mechanisms and the arching effect in the soil embankment. Recently, significant progress has been made, allowing for improvement of the design methods by taking into account the frictional and sliding effects of the geosynthetic sheet in the anchorage areas and the local increase of the vertical stresses in the vicinity of the edges of the cavity. Nevertheless, the soil dilatancy, or the load transfer mechanisms in the embankment during the formation of the cavity or under static or cyclic loadings, remains unknown. Additionally, the reinforced, treated soil layer has not been specifically studied. To focus on the soil embankment behavior over a void, experimental studies were conducted as part of the FUI research project GéoInov. Sinkholes are experimentally simulated under granular embankments and treated soil layers, both reinforced by geotextiles. Each void is created by a device that allows the progressive formation of a circular cavity with an increasing diameter of 0.75, 1.25 and 2.2 m. This enables reproduction of the formation of some natural sinkholes. After the void reaches a size of 2.2 m wide, traffic loads are applied on the top surface of the embankment. Then, during both the formation of the cavity and the vehicle traffic loading, a dedicated instrumentation is used to measure the dilatancy and the soil movement, the load transfer, the deformation of the geotextile and the surface settlement. The experimental results are then analyzed and compared with existing analytical methods to improve the existing analytical methods.